Solitary Fibrous Tumor in the Retroperitoneum A Case Report - Imanaka, Takahiro (Hinyokika kiyo. Acta urologica Japonica, 2016)
A 55-year-old man was diagnosed with an abdominal tumor and referred to our department. Abdominal contrast-enhanced computed tomography revealed a 15-cm tumor in the retroperitoneum. The inferior vena cava was compressed ventrally, the right ureter laterally, and the right kidney toward the head. Part of the tumor was situated on the dorsal side of the abdominal aorta. A preoperative diagnosis of neurogenic tumor or a type of sarcoma was made. We performed en bloc resection of the tumor. The right kidney was also resected. We exfoliated between the tumor and inferior vena cava without temporary interruption. The final diagnosis was a solitary fibrous tumor. The patient received no adjuvant therapy. Neither recurrence nor metastasis has been detected for 8 months postoperatively